Clinical Risk Assessment- An Inevitable Tool in Periodontal Disease Diagnosis: A Short Review - Mahendra, Jaideep; Mahendra, Little; M, Janani; Sharma, (Lt Col) Vivek (International Journal Of Drug Research And Dental Science, 2022)
Background: The ideal dental practice involves identifying patients and populations who are at enhanced risk of developing periodontal disease and treating them with the proper intervention that helps not only in preventing the disease progression but also aids in reducing the severity burden. As dental practitioners look to optimize the therapy and patient outcomes, the function of risk assessment and management is becoming increasingly important. Aim: This article aims in reviewing the application of risk assessment and disease management to the general population and to groups at risk of developing periodontal disease. Review Results: There are various scientific evidences emerging during the recent decades that aids in better understanding of the underlying etiopathogenesis and various risk factors associated with periodontal diseases for their incidence, progression, and severity. Correlating the clinical examination findings with the available diagnostic investigations has become a primary mode of determining the disease prognosis to evaluate the risk assessment ratio in the treatment of periodontal diseases. Conclusion: Risk assessment can aid in the prediction of a patient’s risk of acquiring the periodontal disease and enhance the skills of clinical decision-making. Patient commitment to a self-care oral health routine, in turn, is a critical component of effective periodontal disease management. Clinical Significance: Risk assessment in clinical practice helps in identifying the higher risk group of disease exposure, thereby predicting the future outcomes of the disease and thus helps in minimizing the need for invasive periodontal therapy, improve patient treatment outcomes, and, ultimately, lower the oral health care expenditures. Such patients are thus advised to take an active role in maintaining oral health care by brushing, flossing, and rinsing with an antimicrobial mouth rinse on a regular basis.